1999
DOI: 10.1016/s0092-8674(00)80965-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional Association of Nmi with Stat5 and Stat1 in IL-2- and IFN γ-Mediated Signaling

Abstract: Using the coiled-coil region of Stat5b as the bait in a yeast two-hybrid screen, we identified the association of Nmi, a protein of unknown function previously reported as an N-Myc interactor. We further show that Nmi interacts with all STATs except Stat2. We evaluated two cytokine systems, IL-2 and IFNgamma, and demonstrate that Nmi augments STAT-mediated transcription in response to these cytokines. Interestingly, Nmi lacks an intrinsic transcriptional activation domain; instead, Nmi enhances the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
241
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(253 citation statements)
references
References 60 publications
11
241
0
1
Order By: Relevance
“…52 The PPARs have been implicated in a wide range of biological processes, including cell growth, lipid homeostasis, apoptosis and inflammation. 53 Notably, an additional transcriptional co-activator, NMI, which interacts with all STATs (except STAT2) and potentiates their association with the coactivators CBP/p300 54 was upregulated in all three strains by 3 h IFN-a stimulation and significantly overexpressed in MRL/lpr and BALB/c mice at 3 h time point. Interestingly, NMI and CITED2 exhibited different responses to IFN-a treatment in two lupus-prone strains.…”
Section: Discussionmentioning
confidence: 99%
“…52 The PPARs have been implicated in a wide range of biological processes, including cell growth, lipid homeostasis, apoptosis and inflammation. 53 Notably, an additional transcriptional co-activator, NMI, which interacts with all STATs (except STAT2) and potentiates their association with the coactivators CBP/p300 54 was upregulated in all three strains by 3 h IFN-a stimulation and significantly overexpressed in MRL/lpr and BALB/c mice at 3 h time point. Interestingly, NMI and CITED2 exhibited different responses to IFN-a treatment in two lupus-prone strains.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestive of such an alteration, it is noteworthy that the electrophoretic mobility of STAT3 complexes consistently decreased after 3 days of culture (Figure 1). Recently, it was shown that the N-Myc interactor (Nmi) protein associates with di erent STAT proteins, including STAT3, and augments STAT-induced transcription by enhancing recruitment of the coactivator proteins CBP/p300 (Zhu et al, 1999). The fact that Nmi expression is induced by multiple cytokines provides a novel mechanism for speci®c enhancement of STAT transcriptional activity by growth factors, including G-CSF, which may be relevant in this context.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Sp1 has been reported to interact with Stat1 (Look et al, 1995), cJun with Stat3b (Schaefer et al, 1995), MCM5 with Stat1a (Zhang et al, 1998a), and the glucocorticoid receptor with Stat3, Stat5a, and Stat5b (Cella et al, 1998;Stocklin et al, 1996;Zhang et al, 1997). In addition, coactivators CBP/p300 have been shown to interact with Stat1, Stat2, Stat5a, Stat5b and Stat6 (Bhattacharya et al, 1996;Gingras et al, 1999;P®tzner et al, 1998;Zhang et al, 1996;Zhu et al, 1999). Nmyc interacting protein (Nmi) was shown to associate with Stat5b in a yeast two-hybrid interaction trap and by coprecipitation (Zhu et al, 1999).…”
Section: How Do Stat5 Proteins Regulate Transcription Of Target Genes?mentioning
confidence: 99%
“…In addition, coactivators CBP/p300 have been shown to interact with Stat1, Stat2, Stat5a, Stat5b and Stat6 (Bhattacharya et al, 1996;Gingras et al, 1999;P®tzner et al, 1998;Zhang et al, 1996;Zhu et al, 1999). Nmyc interacting protein (Nmi) was shown to associate with Stat5b in a yeast two-hybrid interaction trap and by coprecipitation (Zhu et al, 1999). The exact mechanism(s) by which these transcription factors and coactivators integrate their e ects into the signals mediated by STAT proteins require further work, but it seems that ubiquitously expressed coactivators CBP/ p300 are generally important for STAT-mediated transcription.…”
Section: How Do Stat5 Proteins Regulate Transcription Of Target Genes?mentioning
confidence: 99%